Efektivitas Gaya Kepemimpinan Tuan Guru dalam Tata Kelola Pondok Pesantren - Mahsar Mahsar (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
This study aims to determine: 1) Tuan Guru's leadership style at Darul Abror NW Gunung Rajak Islamic Boarding School and Darul Furqon NW Mengkuru Islamic Boarding School; 2) similarities and differences in the Tuan Guru leadership style at Darul Abror NW Gunung Rajak Islamic Boarding School and Darul Furqon NW Mengkuru Islamic Boarding School; and 3) the effectiveness of governance at the Darul Abror NW Gunung Rajak Islamic Boarding School and the Darul Furqon NW Mengkuru Islamic Boarding School). The method used in this research is descriptive qualitative. Data collected by observation, interviews, and documentation. The results of this study are: 1) Tuan Guru's leadership style at Darul Abror Islamic Boarding School NW Gunung Rajak emphasizes exemplary, competency-based recruitment, formation of management through deliberations, and collaborative program arrangement, while Tuan Guru's leadership style at Darul Furqon Islamic Boarding School NW Mengkuru involves a clear pattern of assignments, recruitment based on qualifications, formation of management through deliberations, and preparation of activity programs through deliberations led by Tuan Guru; 2) the similarity of Tuan Guru's leadership style at Darul Abror NW Gunung Rajak Islamic Boarding School and Darul Furqon NW Mengkuru Islamic Boarding School is that both used a spiritual-based leadership style, while the difference is that Tuan Guru at Darul Abror NW Gunung Rajak Islamic Boarding School used a visionary leadership style, while Tuan Guru's leadership style is in Darul Furqon Islamic Boarding School NW Mengkuru used a charismatic leadership style; 3) Governance at the Darul Abror NW Gunung Rajak Islamic Boarding School looks effective by using a model of responsibility-based governance, regeneration and professionalism, while governance at the Darul Furqon NW Mengkuru Islamic Boarding School also looks effective with responsibility-based governance and loyalty.